Relationship between ganglion cell complex thickness and brief presentation stimuli ‐ visual acuity across foveal and parafoveal locations in healthy eyes - Pérez‐Carrasco, M°. Jesús; Silva, Erika Sarco; Marcos, Claudia Sacristán; Puell, María (Acta ophthalmologica (Oxford, England), 2022)
Purpose: Knowledge of the retinal structure ‐ visual function relationship of healthy eyes would be important to the early detection of neuropathies of the retina. This study investigated the association between brief presentation stimuli ‐ visual acuity (BPS‐VA) and the thicknesses of the retina in healthy young eyes. Methods: Photopic and high‐mesopic BPS‐VA was measured in 35 healthy eyes of 35 young subjects (24.3 ± 3.1 years) with the Acuity‐Plus test in the fovea and the parafovea (5° eccentricity) using an optotype presentation of duration 160 ms. The macular thicknesses of the central fovea, parafovea, and macular ganglion cell complex (mGCC), and the thickness of the peripapillary retinal nerve fibre layer (pRNFL) were measured by spectral‐domain optical coherence tomography (SD‐OCT). Relationships between foveal and parafoveal BPS‐VA and the retinal thickness in the corresponding region were examined after adjusting for confounding variables. Results: In photopic luminance conditions, the inferior mGCC thickness was the only structural significant predictor to the foveal BPS‐VA (p = 0.007). Under high‐mesopic level, retinal illuminance and inferior mGCC thickness were contributing factors to the foveal BPS‐VA (p = 0.001). Retinal thicknesses were not predictors of parafoveal BPS‐VA at any of the light levels. Conclusions: The inferior mGCC thickness predicts foveal BPS‐VA measured at both photopic and high‐mesopic light levels in healthy eyes of young subjects.